Assessment of Road Noise Pollution in Urban Residential Areas—A Case Study in Piteşti, Romania - Aurel Mihail Titu; Andrei Alexandru Boroiu; Sorin Mihailescu; Alina Bianca Pop; Alexandru Boroiu (Applied Sciences, 2022)
The paper addresses the problem of urban road noise, in the context of the European legislative requirements regarding noise pollution. The second noise mapping in Pitesti city, revealed that despite the proposed action plan after the first noise mapping, the noise pollution increased instead of decreasing. Considering that the proposed measures were insufficient to control road noise in the conditions of the estimated increase in road traffic, the authors developed complex research to identify how the road noise level is determined by the way of regulation of road traffic at intersections of the residential zone. Thus, noise and traffic measurements are made at the main road intersections in the central part of the city, determining the most relevant noise indicators for the specifics of urban traffic and residential areas. The results obtained lead to the conclusion that roundabouts bring a reduction in noise pollution compared to traffic light intersections only if the speed of vehicles in the roundabout is predictable: on preselected lanes and with speed timing.